Clinical Pharmacogenetics Implementation Consortium (CPIC) Guideline for CYP2C19 and Proton Pump Inhibitor Dosing. Issue 6 (20th September 2020) - Lima, John J.; Thomas, Cameron D.; Barbarino, Julia; Desta, Zeruesenay; Van Driest, Sara L.; El Rouby, Nihal; Johnson, Julie A.; Cavallari, Larisa H.; Shakhnovich, Valentina; Thacker, David L.; Scott, Stuart A.; Schwab, Matthias; et al.
Abstract : Proton pump inhibitors (PPIs) are widely used for acid suppression in the treatment and prevention of many conditions, including gastroesophageal reflux disease, gastric and duodenal ulcers, erosive esophagitis, Helicobacter pylori infection, and pathological hypersecretory conditions. Most PPIs are metabolized primarily by cytochrome P450 2C19 (CYP2C19) into inactive metabolites, and CYP2C19 genotype has been linked to PPI exposure, efficacy, and adverse effects. We summarize the evidence from the literature and provide therapeutic recommendations for PPI prescribing based on CYP2C19 genotype (updates at www.cpicpgx.org ). The potential benefits of using CYP2C19 genotype data to guide PPI therapy include (i) identifying patients with genotypes predictive of lower plasma exposure and prescribing them a higher dose that will increase the likelihood of efficacy, and (ii) identifying patients on chronic therapy with genotypes predictive of higher plasma exposure and prescribing them a decreased dose to minimize the risk of toxicity that is associated with long‐term PPI use, particularly at higher plasma concentrations.